Maternal Mortality and Risk Factors among Pregnant Women with COVID‑19 in Isolation Centers of Al‑Bayda, Derna, and Tobrouk - Abtisam Alsaliheen; Amna Kalefa; Halima Alhassi (AlQalam Journal of Medical and Applied Sciences, 2026)
The COVID-19 pandemic has shown high mortality and morbidity among pregnant women worldwide. This study aimed to estimate the case fatality rate and identify risk factors among pregnant women with COVID-19 infection admitted to the ICU and isolation centers in Al-Bayda, Derna, and Tobrouk, Libya, from 2020 to 2021. A case series study was conducted reviewing records of pregnant women admitted to isolation centers for COVID-19 infection. Statistical analysis was performed using SPSS 23.0. COVID-19 in pregnancy demonstrated a high maternal mortality rate of 14.3% and a high rate of fetal loss at 25%. Lower hemoglobin levels, higher leukocyte count, and elevated erythrocyte sedimentation rate were significantly associated with complicated cases. COVID-19 in pregnancy has a high maternal mortality rate and a high rate of fetal loss. The finding of hemoglobin, leukocyte count, and erythrocyte sedimentation rate differences is worthy of further research in predicting mortality and disease severity for similar infections among pregnant women.